Integrated Parking Spaces Arrangement in Commercial Areas (Case Study: Cirebon City) - Abu Nidal, Haikal; Agustina, Ardianti; Farhan, Ohan; Lestira Hariani, Mira (Jurnal Sosial Teknologi, 2024)
The effect of on street parking in urban commercial areas can cause a degradation of road performance. Therefore, the development of an integrated parking system is crucial to be carried out in commercial areas so that the performance of road sections does not degrade and does not cause heavy congestion. This study aims to provide recommendations for integrated parking locations based on existing parking conditions in the study area, so that they can be integrated and combined in one location. The method used is a primary survey that refers to the guidelines of the Indonesian Road Capacity Manual (IRCM) 1997 in analyzing traffic performance, and refer to the Guidelines for the Implementation of Parking Facilities 1997 in analyzing parking conditions. Meanwhile, for recommendations in determining alternative parking locations using SWOT analysis. The result of this research is the proposed location for integrated parking at Pasar Balong with the recommendation of a 4-floor building. The SWOT analysis showed that its strengths are its strategic location and high parking demand, its weaknesses are land limitations and lack of integrated parking management, its opportunities are potential for revenue and increased traffic flow, and its threats are resistance from local businesses and significant investment needs. The implication of this study is to provide a solution to the problem of roadside parking in commercial areas that interfere with traffic flow, improve the efficiency and accessibility of parking facilities for the community, and become a reference for further research on integrated parking management in other commercial areas.